THE ROLE OF LANGUAGE ASSESSMENT IN EFFECTIVE SECOND LANGUAGE ACQUISITION - Khamida Ganieva Utkir qizi, (Ustozlar uchun, 2025)
This article explores the pivotal role of language assessment in second language acquisition (SLA), emphasizing its function beyond simple testing to encompass improved teaching and learner support. It defines language assessment as a broad range of formal and informal methods for measuring language skills, highlighting the importance of reliability, validity, practicality, and benefit to learners. The article details how assessment aids in identifying proficiency levels, motivating students, and providing crucial feedback. It further differentiates between formative, summative, diagnostic, placement, and proficiency tests, outlining their specific purposes in the SLA process. Ultimately, the article posits that effective language assessment is a continuous, interactive process that shapes both instruction and learning for optimal outcomes in SLA.